THE IMPORTANCE OF SOCIAL AND LEGAL NORMS IN THE UPBRINGING OF THE YOUNGER GENERATION - Abdullayeva M. D. (Modern American Journals, 2025)
The article explores the importance of social and legal norms in the upbringing of the younger generation, emphasizing their decisive role in shaping responsible and law-abiding citizens. The study focuses on how the integration of ethical values, cultural traditions, and legal awareness contributes to the moral and intellectual development of youth. It highlights the fact that social norms create a foundation for interpersonal relationships, respect for others, and collective solidarity, while legal norms provide a framework for justice, responsibility, and protection of rights. The analysis underscores the interconnectedness of these two categories, showing that without the proper balance of social and legal norms, it becomes difficult to ensure sustainable personal growth and civic consciousness. The article also draws attention to the role of educational institutions, families, and communities in instilling these values in the daily lives of children and adolescents. By synthesizing theoretical perspectives and practical examples, the research argues that education systems must incorporate social and legal education as a central component of curricula to promote not only academic achievement but also moral responsibility and social harmony. The findings suggest that fostering respect for both social and legal norms in young people creates conditions for a stable, tolerant, and law-abiding society.
Keywords: Social norms, legal norms, upbringing, civic responsibility, education, morality, ethics, law, youth development, pedagogy.